Pore-Throat Differences Across Flow Units in Low-Permeability Sandstone Reservoirs: Impact on Movable Fluid Saturation in the Triassic Chang 6 Reservoir, Jiyuan Oilfield, Ordos Basin, China - Pan Li; Jian Yan; Rui Hu; Ming Han; Jiangang Bai (Geofluids)
Low-permeability sandstone reservoirs, as a subset of unconventional oil and gas reservoirs, have gained significant attention due to their distinct exploration and development potential. These reservoirs exhibit intricate heterogeneity, variable seepage behaviors, and complex remaining oil distribution. As a result, comprehensive research is crucial to optimize exploration and development activities. In this study, we focused on the Chang 6 reservoir in Jiyuan Oilfield, Ordos Basin—a representative low-porosity and low-permeability reservoir. We delved into the pore-throat structure and seepage mechanisms of various flow units, which are characterized as spatially continuous reservoir segments with uniform petrophysical properties and consistent seepage dynamics. These investigations are critical for improving reservoir characterization, pinpointing the distribution of remaining oil, and forecasting reservoir development and production outcomes. This study integrated several methods, including nuclear magnetic resonance experiments, constant-rate mercury intrusion, high-pressure mercury intrusion, image particle sizing, scanning electron microscopy, and pore-casted thin sections. Our results indicate that different flow units adhere to unique dynamic fluid occurrence patterns. To evaluate the flow units of the Chang 6 member reservoir in the Jiyuan Oilfield, we considered five parameters: sand thickness, porosity, permeability, oil saturation, and flow zone index. Based on microscopic pore structure characteristics and their influence on movable fluid saturation, we classified flow units into four types: excellent (E), good (G), moderate (M), and poor (P). We observed that the microscopic pore structures among these four flow unit types differ considerably, which in turn affects the states of the movable fluids within them. There is a weaker correlation between the pore-throat radius ratio and the movable fluid saturation in reservoirs (R2=0.4047), whereas there is a stronger correlation between movable fluid saturation and throat radius (R2=0.8434). Notably, the throat radius distribution and the main-flow throat radius emerged as key determinants. During the exploration and development stages, Type E and Type G flow units showed the most promising production potential. As a result, it is imperative to craft development strategies that align with the microscopic pore structures unique to each flow unit.